Home, safe home: Cross-country monitoring framework for vulnerabilities in the residential real estate sector - Elias Bengtsson; Magdalena Grothe; Etienne Lepers (European Central Bank (ECB), 2017)
This paper proposes a framework for monitoring vulnerabilities related to the residential real estate sector in a cross-country context. The framework might be useful for complementing or cross-checking signals available from existing approaches. It takes into account three dimensions of real estate sector vulnerabilities (i.e. valuation, household indebtedness and the bank credit cycle) and enables monitoring across countries in a simple and informative way. Indicators are derived from the early warning literature and policy publications. They are aggregated in a modelfree way to a vulnerability measure, explicitly capturing the level and the dynamics of vulnerabilities. The measure proves to be a significant predictor of historical real estate crises, with a better forecasting performance than the majority of advantageously in-sample calibrated model-based estimates. The monitoring framework allows for a simple and transparent analysis across different dimensions, provides a cross-check of consistency of signals from several indicators, and accounts for the developments in terms of the levels and dynamics. In view of its good forecasting performance, it is a useful complement of model-based toolkits for analysing vulnerabilities in the residential real estate sector.
Keywords: R31; E32; C53; 330; real estate vulnerabilities; real estate crises; early warning models; risk monitoring